The Majority of Accredited Continuing Professional Development Activities Do Not Target Clinical Behavior Change. (February 2015) - Légaré, France; Freitas, Adriana; Thompson-Leduc, Philippe; Borduas, Francine; Luconi, Francesca; Boucher, Andrée; Witteman, Holly O.; Jacques, André
<x xml:space="preserve">Abstract</x> Purpose Continually improving patient outcomes requires that physicians start new behaviors, stop old behaviors, or adjust how they practice medicine. Continuing professional development (CPD) is the method most commonly used by physicians to improve their knowledge and skills. However, despite regular physician attendance at these activities, change in clinical behavior is rarely observed. The authors sought to identify which of Bloom's domains (cognitive, affective, or psychomotor) are targeted by the learning objectives of CPD activities offered by medical associations, regulatory bodies, and academic institutions in the province of Quebec, Canada. Method The authors evaluated the objectives of 110 accredited CPD activities offered to physicians and other health professionals from November 2012 to March 2013. The objectives of each activity were extracted and classified into learning domains using Bloom's taxonomy. Results Ninety-six percent of the learning objectives analyzed targeted the cognitive domain, which consists of six levels of increasing complexity: knowledge, comprehension, application, analysis, synthesis, and evaluation. Half (47%) targeted knowledge and comprehension, whereas only 26% aimed to improve skills in analysis, synthesis, and evaluation. Conclusions Most accredited CPD activities within this sample were generally not designed to promote clinical behavior change because the focus of these activities was on remembering and understanding information instead of preparing physicians to put knowledge into practice by analyzing information, evaluating new evidence, and planning operations that lead to behavior change. Educators and CPD providers should take advantage of well-established theories of health professional behavior change, such as sociocognitive theories, to develop their activities.